The relationship of redox potential to crustacea abundance at Bama beach of Baluran National Park, Situbondo, Indonesia - Hariyadi Hariyadi; Dony Prasetyo; Yuni Dwi Kurniawati (Universitas Muhammadiyah Malang, 2020)
Catfish farming is growing rapidly because the cultivation and marketing technology is relatively easy for the community to master, and the required business capital is relatively small. Pond water waste originating from fish metabolism and dissolved food waste is toxic to fish. One of the efforts that can be done is fish farming that is integrated with plants through an aquaponics system. Research to determine the effect of AB Mix addition on the growth of African catfish and lettuce cultivated by the aquaponics system. The research method used was an experimental method with a completely randomized design (CRD) consisting of three treatments and three replications. The addition of AB mixed nutrition did not differ in the growing significance of catfish and lettuce. However, the increase in growth occurred with an increasing dosage of AB mix with the best treatment with AB Mix 3 mL L-1. This treatment resulted in absolute growth in fish of 20.52 g and 4.62 g of watercress. The use of a dosage of AB mix higher than 3 mL L-1 may result in better growth.